2020
DOI: 10.1093/tas/txaa074
|View full text |Cite
|
Sign up to set email alerts
|

Average daily gain divergence in beef steers is associated with altered plasma metabolome and whole blood immune-related gene expression

Abstract: We evaluated the plasma amine/phenol- and carbonyl-metabolome and whole-blood immune gene expression profiles in beef steers with divergent average daily gain. Forty-eight Angus crossbred beef steers (21 d post-weaning; 210 ± 8.5 kg of body weight) were fed the same total mixed ration ad libitum for 42 d with free access to water. After 42 d of feeding, the steers were divided into two groups of lowest (LF: n = 8) and highest average daily gain (HF: n = 8). Blood samples were taken from all steers. The blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We identified that unclassified Clostridiales (OTU 1000113) was a key contributor to the synthesis of anthranilate, while Akkermansia muciniphila (OTU 358757) was predicted to contribute to the degradation of tryptamine and the synthesis of 4,6-dihydroxyquinoline. Anthranilate, tryptamine, and 4,6-dihydroxyquinoline are all tryptophan metabolites [54][55][56], and tryptophan metabolites are well established as ligands for the AhR [42] and modulate inflammation in multiple cell types [30,57]. Tryptophan metabolism also plays an important role in impeding CRC development through inhibiting inflammation, repairing the gut barrier structure, and interacting with beneficial microorganisms in the gut [57].…”
Section: Discussionmentioning
confidence: 99%
“…We identified that unclassified Clostridiales (OTU 1000113) was a key contributor to the synthesis of anthranilate, while Akkermansia muciniphila (OTU 358757) was predicted to contribute to the degradation of tryptamine and the synthesis of 4,6-dihydroxyquinoline. Anthranilate, tryptamine, and 4,6-dihydroxyquinoline are all tryptophan metabolites [54][55][56], and tryptophan metabolites are well established as ligands for the AhR [42] and modulate inflammation in multiple cell types [30,57]. Tryptophan metabolism also plays an important role in impeding CRC development through inhibiting inflammation, repairing the gut barrier structure, and interacting with beneficial microorganisms in the gut [57].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the growth performance of LF and HF steers have been previously reported [ 8 ]. Briefly, the average initial body weight (229 vs. 225 kg; SE = 5.21) and average daily DM intake (6.08 vs. 6.04 kg; SE = 0.23) of the LF and HF beef steers were similar ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…All experimental animals were managed according to guidelines approved by the Institutional Animal Care and Use Committee of Kentucky State University (18-0001). Details about animals, feeding, and measurements of dry matter intake and average daily gain have been reported previously [ 8 ]. Briefly, 48 Angus crossbred beef steers (21 d post-weaning; 210 ± 8.5 kg of body weight) were individually housed in slatted floor pens (2.44 × 14.63 m 2 ) and fed ad libitum a 79% corn silage and 21% grain mix-based total mixed ration with free access to water for 42 d after a 21 d adaptation period (63 d total).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation